PENGARUH PENGETAHUAN PERPAJAKAN, SELF-EFFICACY DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA BERKARIR SEBAGAI KONSULTAN PAJAK - Minardo, Minardo Sihombing (SCIENTIA JOURNAL, 2024)
The tax consultant profession in Batam City is still small; this is due to the low interest of accounting students in a career as a tax consultant. Factors causing low student interest in a career as a tax consultant include taxation knowledge, self-efficacy, and labor market considerations. This study aims to determine whether taxation knowledge, self-efficacy, and labor market considerations affect the interest of accounting students in a career as a tax consultant. The data analysis method used in this study consists of descriptive statistical tests, data quality tests consisting of validity tests and reliability tests, classical assumption tests, multiple linear regression tests, determination coefficient tests, and hypothesis tests consisting of t tests and f tests. The hypothesis in this study shows that partially taxation knowledge, self-efficacy, and labor market considerations have a positive and significant effect on the interest of accounting students in a career as a tax consultant, and simultaneously, taxation knowledge, self-efficacy, and labor market considerations have a positive and significant effect on the interest of accounting students in a career as a tax consultant. The test of the coefficient of determination in this study amounted to 0.397, or 39.7%, of the variable accounting student interest in a career as a tax consultant. Meanwhile, the remaining 60.3% is influenced by variables not identified in this study.